STEM-Based Fire Disaster Mitigation Training to Foster Safety Awareness Among Early Childhood Education Students - Ina Ana Khoeriah; Della Apriyani Kusuma Putri; Lucky Dewanti; Herman Hadiwijaya (CV. Dharma Samakta Edukhatulistiwa, 2026)
Fire disasters constitute one of the most serious threats that can occur within school environments, including at the Early Childhood Education (ECE) level. However, fire disaster mitigation programs specifically designed for young children remain considerably limited, particularly those integrating innovative learning approaches. This gap underscores the necessity for educational interventions aligned with the cognitive and psychomotor developmental stages of early childhood. In response, this community service program aimed to cultivate safety awareness and fundamental fire disaster mitigation skills among ECE students through STEM (Science, Technology, Engineering, and Mathematics)-based training. The implementation method employed a Participatory Action Research (PAR) approach combined with interactive training and mentoring, encompassing the dissemination of fire safety materials, evacuation drills, and hands-on activities involving the construction of simple teaching aids representing firefighting equipment used to extinguish fires. This program was conducted at TKIT AR RAUDLOH, Kuningan Regency, involving 30 students from Groups A and B along with 4 accompanying teachers. The findings demonstrated a significant improvement in students' understanding of fire hazards, their ability to perform basic evacuation procedures, and high levels of enthusiasm in STEM-based activities. In conclusion, STEM-based fire disaster mitigation training serves as an effective educational solution for fostering safety awareness from an early age and can be sustainably implemented within ECE settings.